Candida albicans and Staphylococcus Species: A Threatening Twosome - Carolus, Hans; Van Dyck, Katrien; Van Dijck, Patrick (Frontiers in Microbiology, 2019)
C. albicans and Staphylococcus species are respectively the most common fungal and bacterial agents isolated from bloodstream infections, worldwide. Moreover, it has been shown that 20% of all C. albicans bloodstream infections are polymicrobial in nature, with S. epidermidis and S. aureus being the first and third most common co-isolated organisms, respectively. These species are part of the commensal microbial flora but can cause hospital-acquired infections with an extreme ability to inhabit diverse host niches, especially in immunocompromised patients. They are well known for their ability to form persistent biofilms in the host or on abiotic surfaces such as indwelling medical devices. Interactions within these biofilm communities can lead to increased virulence, drug tolerance and immune evasion. This can ultimately impact morbidity and infection outcome, often leading to an increased mortality. Therefore, characterizing the interactions between these species could lead to the development of novel therapeutic approaches that target polymicrobial infections. In this mini review we briefly highlight the current knowledge and most recent insights into the complex interspecies interactions of C. albicans with Staphylococcus bacteria